2011
DOI: 10.1016/j.bmc.2010.10.029
|View full text |Cite
|
Sign up to set email alerts
|

A systematic protocol for the characterization of Hsp90 modulators

Abstract: Several Hsp90 modulators have been identified including the N-terminal ligand geldanamycin (GDA), the C-terminal ligand novobiocin (NB), and the co-chaperone disruptor celastrol. Other Hsp90 modulators elicit a mechanism of action that remains unknown. For example, the natural product gedunin and the synthetic anti-spermatogenic agent H2-gamendazole, recently identified Hsp90 modulators, manifest biological activity through undefined mechanisms. Herein, we report a series of biochemical techniques used to clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
83
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(85 citation statements)
references
References 46 publications
2
83
0
Order By: Relevance
“…The molecular mechanism of action related to the biologic effects of gedunin relies on the inhibition of Hsp90 activity via specific binding to the cochaperone p23 and by disrupting the cochaperone Cdc37-Hsp90 interaction (Matts et al, 2011;Patwardhan et al, 2013). However, here we demonstrate that gedunin mechanisms of action go beyond Hsp90 modulation.…”
Section: Introductionmentioning
confidence: 56%
See 1 more Smart Citation
“…The molecular mechanism of action related to the biologic effects of gedunin relies on the inhibition of Hsp90 activity via specific binding to the cochaperone p23 and by disrupting the cochaperone Cdc37-Hsp90 interaction (Matts et al, 2011;Patwardhan et al, 2013). However, here we demonstrate that gedunin mechanisms of action go beyond Hsp90 modulation.…”
Section: Introductionmentioning
confidence: 56%
“…Hsp90 is an abundantly and ubiquitously expressed chaperone that helps to maintain, at the expense of ATP, the structure of several membrane, cytoplasmic, and endoplasmic reticulumassociated client proteins (Pratt and Toft, 1997;Picard, 2002;Zhao and Houry, 2005;McClellan et al, 2007). Hsp90 chaperoning activity can be inhibited by geldanamycin, 17-allylamino-17-demethoxy-geldanamycin (17-AAG), and celastrol, which leads to increased degradation of Hsp90 client proteins (Matts et al, 2011). In experimental models, Hsp90 inhibitors have been shown to suppress different signaling pathways and display potent antiproliferative, cytoprotective, and anti-inflammatory activities (Lewis et al, 2000;Poulaki et al, 2007;Ambade et al, 2012;Chow et al, 2013;Leung et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In a series of subsequent studies, photoaffinity labeling and proteolysis studies were incorporated into experimentally guided computational predictions to characterize the allosteric C-terminal binding site in Hsp90 at atomic resolution. [198,199] These studies have confirmed that targeted allosteric modulators can antagonize the chaperone function by inducing a conformationally favorable separation of the Hsp90-CTDs and thereby interfere with Hsp90 dimerization. This explained the biological activities of novobiocin and other Hsp90 modulators, providing a new paradigm for the development of allosteric inhibitors to target the C-terminal binding pocket.…”
Section: Hsp90 and Client Proteinsmentioning
confidence: 62%
“…These interact with HSP90 at non-overlapping sites as demonstrated by their ability to capture HSP90 in distinct conformational states [90]. …”
Section: Ligands Targeting the Major Chaperonesmentioning
confidence: 99%